The chemokine CXCL1/growth related oncogene increases sodium currents and neuronal excitability in small diameter sensory neurons - Wick Dayna M; Coyle Dennis E; Yang Rui-Hua; Xie Wenrui; Strong Judith A; Wang Jun-Gang; Dorsey Ericka D; Zhang Jun-Ming (SAGE Publishing, 2008)
Abstract Background Altered Na+ channel expression, enhanced excitability, and spontaneous activity occur in nerve-injury and inflammatory models of pathological pain, through poorly understood mechanisms. The cytokine GRO/KC (growth related oncogene; CXCL1) shows strong, rapid upregulation in dorsal root ganglion in both nerve injury and inflammatory models. Neurons and glia express its receptor (CXCR2). CXCL1 has well-known effects on immune cells, but little is known about its direct effects on neurons. Results We report that GRO/KC incubation (1.5 nM, overnight) caused marked upregulation of Na+ currents in acutely isolated small diameter rat (adult) sensory neurons in vitro. In both IB4-positive and IB4-negative sensory neurons, TTX-resistant and TTX-sensitive currents increased 2- to 4 fold, without altered voltage dependence or kinetic changes. These effects required long exposures, and were completely blocked by co-incubation with protein synthesis inhibitor cycloheximide. Amplification of cDNA from the neuronal cultures showed that 3 Na channel isoforms were predominant both before and after GRO/KC treatment (Nav 1.1, 1.7, and 1.8). TTX-sensitive isoforms 1.1 and 1.7 significantly increased 2 - 3 fold after GRO/KC incubation, while 1.8 showed a trend towards increased expression. Current clamp experiments showed that GRO/KC caused a marked increase in excitability, including resting potential depolarization, decreased rheobase, and lower action potential threshold. Neurons acquired a striking ability to fire repetitively; IB4-positive cells also showed marked broadening of action potentials. Immunohistochemical labelling confirmed that the CXCR2 receptor was present in most neurons both in dissociated cells and in DRG sections, as previously shown for neurons in the CNS. Conclusion Many studies on the role of chemokines in pain conditions have focused on their rapid and indirect effects on neurons, via release of inflammatory mediators from immune and glial cells. Our study suggests that GRO/KC may also have important pro-nociceptive effects via its direct actions on sensory neurons, and may induce long-term changes that involve protein synthesis.